2009
DOI: 10.1121/1.3021437
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic, psychophysical, and neuroimaging measurements of the effectiveness of active cancellation during auditory functional magnetic resonance imaging

Abstract: Functional magnetic resonance imaging (fMRI) is one of the principal neuroimaging techniques for studying human audition, but, paradoxically, it generates an intense background sound which hinders listening performance and confounds measures of the auditory response. This paper reports the perceptual effects of an active noise control (ANC) system that operates in the electromagnetically hostile and physically compact neuroimaging environment to provide significant noise reduction, without interfering with ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 42 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…during sentence comprehension). Others have endeavoured to reduce the magnitude or impact of the acoustic scanner noise itself by noise cancellation or manipulating the parameters of the acquisition sequence (Hall et al, 2009;Peelle et al, 2010;Schmitter et al, 2008). For a helpful and succinct description of these approaches, we highly recommend Peelle (2014).…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…during sentence comprehension). Others have endeavoured to reduce the magnitude or impact of the acoustic scanner noise itself by noise cancellation or manipulating the parameters of the acquisition sequence (Hall et al, 2009;Peelle et al, 2010;Schmitter et al, 2008). For a helpful and succinct description of these approaches, we highly recommend Peelle (2014).…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…The nonadaptive spectral subtraction algorithm proposed in this study that cascades with the ANC algorithm has shown its effectiveness for further removing the MRI acoustic noise after treatment by the ASE system (see Figs. 8,9). This achievement implies that it is desirable to develop combined adaptive and non-adaptive speech enhancement algorithms where an online/offline post-processing algorithm can be applied to the contaminated speech and achieve a better result.…”
Section: Discussionmentioning
confidence: 93%
“…The acoustic noise during magnetic resonance imaging (MRI) operation remains a major concern, considering MRI is increasingly applied for medical diagnosis and biomedical research [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The primary excitation source of the scanner-emitted acoustic noise is produced by Lorentz forces that physically excite the structural components of the MRI scanner, radiating loud noise due to the structural-acoustic coupling with the surrounding air.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach to reducing the impact of acoustic noise in the MRI scanner is to change the way this sound is perceived by listeners using active noise control (Hall et al, 2009). As typically implemented, active noise control involves measuring the properties of the scanner noise, and generating a destructive acoustic signal (also known as “antinoise”) which is sent to the headphones that cancels a portion of the scanner noise (Chambers et al, 2001, 2007; Li et al, 2011).…”
Section: Solutions For Auditory Fmrimentioning
confidence: 99%
“…Active noise control can reduces the level of acoustic noise by 30–40 dB, and subjective loudness by 20 dB (the difference between these measures likely reflecting the contribution of bone conducted vibration) (Hall et al, 2009; Li et al, 2011). Particularly relevant is that when using relatively simple auditory stimuli (pure tone pitch discrimination), (1) behavioral performance in the scanner was significantly better and (2) activity in primary auditory regions was significantly greater under conditions of active noise control compared to normal presentation (Hall et al, 2009).…”
Section: Solutions For Auditory Fmrimentioning
confidence: 99%